Before she was Harriet : the story of Harriet Tubman - Cline-Ransome, Lesa (Holiday House, 2017)
A lush and lyrical biography of Harriet Tubman, written in verse. An evocative poem and opulent watercolors come together to honor a woman of humble origins whose courage and compassion make her larger than life.